Evaluation of the Mechanical Properties of Surface Modified Ukam Fibre Reinforced Polyester Composites - Okpanachi, G. E.; Abugh, A.; Nyior, G. B.; Suleiman, U. H. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
This work evaluated the properties of ukam fibre reinforced polyester composites. The ukam fibres were subjected to different surface treatments including alkaline, saline, permanganate and acetylation. Composites were produced at 5%, 10%, 15%, 20% and 25% fiber loadings and its mechanical properties determined. The results found that the most suitable mixture for excellent improvement in mechanical properties was obtained with the 25% fibre and 75% resin. Additionally, the results showed improvements in mechanical properties with surface treatments at all fibre loadings. Furthermore, it was observed that Fibre Surface treatment leads to compatibility which resulting in good load transfer between the modified fibre and matrix. Whereas acetylation treated composites exhibited the highest values of hardness at all levels of fibre loading, alkaline treated samples exhibited the highest tensile and compressive strengths at all fibre loadings. It is noteworthy that saline treated composites exhibited highest impact and flexural modulus of rupture. Interestingly, there was no significant improvement noticed with potassium permanganate treated reinforced fibre composites. Therefore, the results clearly showed that alkaline, saline, and acetylation fibre surface treatment methods could be used to produce ukam fibre composites with good mechanical properties for potential engineering applications.